"I Treat Him as a Normal Patient": Unveiling the Normalization Coping Strategy Among Formal Caregivers of Persons With Dementia and Its Implications for Person-Centered Care. (September 2018) - Bentwich, Miriam Ethel; Dickman, Nomy; Oberman, Amitai; Bokek-Cohen, Ya'arit
Introduction: Currently, 47 million people have dementia, worldwide, often requiring paid care by formal caregivers. Research regarding family caregivers suggests normalization as a model for coping with negative emotional outcomes in caring for a person with dementia (PWD). The study aims to explore whether normalization coping mechanism exists among formal caregivers, reveal differences in its application among cross-cultural caregivers, and examine how this coping mechanism may be related to implementing person-centered care for PWDs.Method: Content analysis of interviews with 20 formal caregivers from three cultural groups (Jews born in Israel [JI], Arabs born in Israel [AI], Russian immigrants [RI]), attending to PWDs.Results: We extracted five normalization modes, revealing AI caregivers had substantially more utterances of normalization expressions than their colleagues.Discussion: The normalization modes most commonly expressed by AI caregivers relate to the personhood of PWDs. These normalization modes may enhance formal caregivers' ability to employ person-centered care.